Pengaruh kompetensi dan motivasi kerja terhadap kinerja karyawan pada PT. Elfaatih Global Indonesia - Yulianty, Puspa Dewi; Qodriah, Sari Laelatul; Kurniawan, Pebi; Indriyanti, Hani (Universitas Widya Mataram, 2021)
This study aims to test and determine whether competence and work motivation have an influence on employee performance. The research method used is the verification method with a quantitative approach. The sample used in this research is nonprobability sampling with saturated sampling. So in this study using all populations of 76 respondents. The data analysis technique used in this research is multiple linear regression analysis techniques and to measure the research variables, researchers use a Likert scale. The results of data analysis show that employee competence consisting of intellectual competence, emotional competence and social competence has no influence on the employee performance of PT. EGI. Meanwhile, the results of the data indicate that work motivation which consists of motivator factors and hygiene factors has a strong influence on the performance of the employees of PT. EGI. However, if further tested together the competency and work motivation variables above have a positive and significant effect on the performance of the employees of PT. EGI.